Functional connectomics from resting-state fMRI - Smith, S; Vidaurre, D; Beckmann, C; Beckmann, C; Beckmann, C; Glasser, M; Jenkinson, M; Miller, K; Nichols, T; Nichols, T; Robinson, E; Salimi-Khorshidi, G; et al. (2013)
Spontaneous fluctuations in activity in different parts of the brain can be used to study functional brain networks. We review the use of resting-state functional MRI (rfMRI) for the purpose of mapping the macroscopic functional connectome. After describing MRI acquisition and image-processing methods commonly used to generate data in a form amenable to connectomics network analysis, we discuss different approaches for estimating network structure from that data. Finally, we describe new possibilities resulting from the high-quality rfMRI data being generated by the Human Connectome Project and highlight some upcoming challenges in functional connectomics. © 2013 Elsevier Ltd.